Desenvolvimento de um software didático para o apoio ao aprendizado de ventilação mecânica - Osaku, Erica Fernanda (2005)
This work aims at developing instructional software in the area of Physical Therapy, more specifically in mechanical ventilation. Mechanical ventilation is a subject that students have during the sixth period of the undergraduate course. However, the approach is usually superficial and the students do not have close contact with the ventilator. Also, it is difficult to take a ventilator to the classroom so as to show it to the students, students spend little time during the curricular stage in the Intensive Care Unity. All these factors motivated the development of this software, that comprises texts, figures, short animations, quiz list and, most importantly, clinical cases together with a mechanical ventilation simulator. Knowledge acquisition process was done using text analysis and interviews with an expert. Frames and production rules were used to represent knowledge. The methodology of development included case diagram, data flow diagram and state diagram. The software was completely developed using Macromedia Flash MX 2004. To evaluate the accessibility of the program, two qualitative analyses were done: with undergraduate students and with Physical Therapists work in hospital. The analysis of results indicates that SEVeM accomplished the proposed objective and had good acceptance among users. By using an innovative approach, this software has taken a different view to the students and we believe that it can give support to learning mechanical ventilation in the course, demystifying the equipment and making the subject more attractive. A conclusion can be done from this work in the sense that the use of informatics in Physical Therapy is quite positive, and the computer with educational software is an effective mediator of the teaching/learning process.